Matrimonial offences in the light of Islamic law - Smail, Akakba; Md Hashim, Noraini (2015)
Based on the principle that family is the main entity of the society, this paper highlights the importance of the marital relationship in Islam. As the foundation of the family institution, it is important to provide legal protection to the marital relationship from any harmful act that may damage and threaten the stability of the family. As Islamic law is the main source of family law in most Muslim countries, the analysis of Islamic legal provisions in respect to the marriage contract and its legal effects between the spouses has lead the author to define and classify the matrimonial offences that damage the matrimonial relationship and subsequently the family and society. Based on the general theory of offences in Islamic law and compared (by way of analogy) to the legal effects of a valid marriage contract, matrimonial offences are defined as legally prohibited acts strictly forbidden by Allah relating to the conjugal rights resulting from a valid marriage contract and become fully ascertained after having sexual intercourse. Providing such provisions in a legislative form will enhance the position of the matrimonial relationship as the foundation of the family inadvertently strengthening the society.